The effect of four weeks dynamic warm-up on static and dynamic balance and proprioceptive receptors in skilled female Gymnast - فرشته احمد آبادی; سید محسن آوندی (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: The aim of this study was to investigate the effect of four weeks dynamic warm-up on static and dynamicbalance and proprioceptive receptors in skilled female Gymnast Methodology: For this purpose, 16 skilled femalegymnasts (mean age 9.62±1.45 years, height 130 ±15.62 cm, weight 28.24 ±8.52 kg and BMI 16.27±1.46kg/m2) wereselected and divide into two groups [general warm-up (control), and dynamic stretching] randomly. The firstprotocol included a 10 minute jogging, and the second protocol consisted of jogging and dynamic stretching inmuscles used in performing the skill. Subjects were tested before and after acute protocol and four weeks as the usingdifferent protocols. The indicators of the equilibrium of) anterior-posterior internal-external) in four static (withtwo legs, and with one leg) and dynamic situations (with two legs and one leg) by removing visual input wereinvestigated. Balance assessed with dynamometer system equipped with 7 cameras and Kistler force plate.Statistical analysis of data was performed through ANOVA and the Bonferroni post hoc test at significance levelof (p≤ 0.05). Results: The results of this study showed, a significant increase in dynamic balance with both feetand a feet by removing visual input in a state of equilibrium with a dynamic warm-up protocol after four weeks(p=0.001 Also Static balance on two legs and one foot with a dynamic warm-up protocol was significantlyincreased after four week dynamic protocols respectively (p=0.001, p=0.005). Conclusion: Since the removalof visual inputs can lead to a dysfunction in the postural sway control, Use a dynamic warm-up exercisesdemonstrated in female gymnast that the fluctuations are significantly reduced compared to the control group in away that improves there in the balance performance.